Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi Pada Idx High Dividend 20 Di Bursa Efek Indonesia Tahun 2018-2022 - Nandi Baskoro Saputra; Elen Puspitasari (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to obtain empirical evidence and test the influence of leverage, liquidity, and profitability on firm value which is moderated by dividend policy on the IDX High Dividend on the Indonesia Stock Exchange 2018-2023. This study uses a quantitative approach. Using the purposive sampling method, 62 companies were selected to be used as samples. The analysis method in this research uses multiple regression analysis and moderated regression analysis for moderating variables. The results of this research indicate that leverage, and liquidity have no effect on firm value. Meanwhile, profitability has a significant effect on firm value. Dividend policy as a moderating variable is not able to moderate each independent variable on firm value. Keywords: Dividend policy, Firm Value, Leverage, Liquidity, Profitability